(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. The COVID-19 virus infection can develop ocular manifestations. Purpose. To report a case of a coats disease patient who was evaluated one week before as part of a routine retinal consultation and later had COVID-19 with sudden loss of vision on one eye. Material and Methods. the affected eye had a visual acuity of 20/400. At fundus examination was found abnormal tortuous vasculature, hemorrhages, branch retinal vein occlusion and macular edema. It was confirm with fluorescein angiography and optical coherence tomography. Results. With a combined therapy of intravitreal Aflibercept, periocular triamcinolone and focal laser was recovery the visual acuity to 20/20. Conclusion. There are few cases describes on literature, but a sudden loss of vision during a COVID-19 infection must be early detected and treated to achieve a better visual acuity recovery.